Respuestas
Respuesta dada por:
1
1) 2x + 2y = 1 (4)
2) 3x + 4y = - 1 (-2)
8x + 8y = 4
-6x - 4y = 2
-----------------
2x + 0y = 6
2x = 6
x = 6/2
x = 3
Reemplazo x = 3 en ecuación 1.
2x + 2y = 1
2 (3) + 2y = 1
6 + 2y = 1
2y = 1 - 6
2y = - 5
y = -5/2
Solución :
x = 3
y = -5/2
2) 3x + 4y = - 1 (-2)
8x + 8y = 4
-6x - 4y = 2
-----------------
2x + 0y = 6
2x = 6
x = 6/2
x = 3
Reemplazo x = 3 en ecuación 1.
2x + 2y = 1
2 (3) + 2y = 1
6 + 2y = 1
2y = 1 - 6
2y = - 5
y = -5/2
Solución :
x = 3
y = -5/2
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años
hace 10 años